Communication Audit during Covid-19 Pandemic at Brawijaya University Hospital - Anindyo, Saza Azizah; Kriyantono, Rachmat; Prianti, Desi Dwi (Advances in Social Sciences Research Journal, 2022)
The flow of organizational communication has an influence on organizational effectiveness related to the relationship or implementation and achievement of organizational goals. Moreover, the effectiveness of communication depends on several aspects, such as communication events aspect, organizational communication climate, and organizational communication satisfaction aspect, so that all members of the organization can be motivated to achieve the goals of the organization. In order to have a good communication system, a healthy organization generally shows an open management style, both internal and external openness of the organization. This study aims to analyze the internal communication system at Brawijaya University Hospital (RSUB) regarding employee engagement during the COVID-19 pandemic period of January 2022-July 2022 through a communication audit. The audit process is carried out the Medical Approach or Doctor-Patient Model. For the data collection technique is in the form of questionnaires, namely Organizational Communication Inventory and interviews. The sample used in the form of variation of levels at the Brawijaya University Hospital which it is categorized based on the members of the organization position according to the hierarchy or structure that applies at the University of Brawijaya Hospital with a total of 206 people. The results present that the subordinate indicators have the lowest mean value with the most of the respondents in the low category. It indicates that the communication relationships in the workplace with subordinates need to get attention and improvement between the communication relationships with members of the organization. The lack of good communication relation with subordinates is affected by the lack of appropriateness between the superiors working with one of their subordinates which cause poor communication between the superior and subordinates.